High rate divorce among Muslims in Malaysia: a study of legal reconciliation and Islamic matrimonial dispute remedy - Zakariyah, Luqman; Sapardi @ Saparti, Siti Nurafiqah (2018)
Abstract: Islam encourages parties in conflict to resolve their disputes through amicable settlement and it also introduces Sulḥ as an amiable way to settle matrimonial disputes. This paper deals with the dissolution of marriage among the Muslim community in Malaysia by examining the causes of high rate of divorce and solutions to the social endemic from an Islamic perspective. By this, the paper mainly adopts the qualitative method to study the ways and manner of dissolution of marriage occur among Malaysian Muslims. The study is primarily based on the library resources where the data are collected from classical and contemporary works and treatises on the subject matter. The paper concludes that there is a need for reevaluating the process of Ṣulḥ in the Shariah Courts in settling the dispute between two parties (husband and wife). It argues that the the process of Ṣulḥ in Islamic court should not be seen only as a mode of facilitating the resolution of dissolution of marriage but also to be reckoned as a mechanism for keeping matrimonial relationship healthy and tidy. And by this, the paper proposes a new framework for dispute resolution in the dissolution of marriage based on the hybrid processes (Med-Arb), of alternative dispute resolution (ADR).